Conversion of large diesel engine to run on biogas for high efficiency electrical power generation - Siripornakarachai S. (2014)
This study was to convert and tune a bus diesel engine for electricity production on a farm using biogas as fuel. The engine under study was a Hino K-13CTI 13, 000 cc 24 valve turbocharged engine coupled to a 3 phase 4 pole induction motor to produce electricity at 50 Hz. Modifications included an addition of biogas carburetor for air-fuel mixing, replacing the fuel injection system with spark ignition system, reduction of compression ratio from the original 16:1 to 8:1 using a cylinder head spacer, and modification of the turbocharger waste gate so the boost pressure could be adjusted. When the induction motor was synchronized to the power grid, the running speed of the engine was 1, 500 rpm. Optimal engine efficiency was achieved at 28.6 % by setting the lambda factor at 1.097, ignition timing at 54° before top dead center, and the turbocharger boost at 56 kPa. With this setting, the generator power output was 134.20 kilowatt with emission of CO and NOx being 1, 154 and 896 ppm, respectively. The generator specific output for biogas containing 62 % methane was 1.71 kilowatt-hours per cubic meter of biogas consumed.